29 TO SHARE SCIENCE OR NOT TO: RECOGNIZING FUTON BIAS IN IMMUNOLOGY JOURNALS. (1st March 2005) - Murali, N. S.; Auethavekiat, P.; Murali, H. R.; Erwin, P. J.; Cha, S.; Mueller, P. S.; Ghosh, A. K.
Abstract : Introduction: Full Text on the Net bias (FUTON Bias) is the "tendency to peruse what is more readily available on the Internet." This innate tendency to pick the "low-hanging fruit of convenience" greatly enhances the odds that a FUTON article will be read or cited. By the same token, invisible research, defined as not readily accessible on-line, may possibly be ignored or overlooked and therefore disregarded. Purpose: We sought to determine if there was any effect on the increase in impact factor (IF) of immunology journals which were available FUTON and whether going on-line affected the IF. Methods: A comprehensive search was made to identify all rheumatology and immunology journals worldwide using MEDLINE, PubMed, and EMBASE databases and several search engines. The on-line status of these journals in MEDLINE (as FUTON, abstracts only, and no abstracts or citations) was ascertained. Impact factors for all available journals from 1990 to 2003 were abstracted. Journals that went on-line in the first half of the Internet era (prior to 1998), as opposed to those that went on-line later, were compared using sign rank and rank sum tests. Summary of Results: In general impact factors have increased with the availability of the World Wide Web. As expected the "prior to 1998 era" journals (n = 69) tended to have higher mean impact factors than the post 1998 era journals (n = 58) available as FUTON (2.994 ± 0.793 vs. 0.1.392 ± 0.0.195). Interestingly while FUTON and "abstract only" journals continued to improve their impact factors every year after they went on-line those that had only references or citations without abstracts failed to improve their impact factors. Also "abstract only" journals failed to catch up with the impact factors of their peer journals available as FUTON (p<0.007 year 1 to p<0.01 year 4). Conclusion: This suggests that although the Internet has increased awareness of the existence of a journal, those allowing FUTON access are likely to make substantial leaps in their impact factors and continue to outstrip their peers who fail to provide such access. Also, barrier free access will threaten journals that insist on subscription who need to recognize the looming threat of becoming obscure. The FUTON bias like the "Tower of Babel" bias influences visibility of research and limits consideration of relevant medical literature impeding the progress of evidence based medicine.